On App: A Reward-Based Classroom Management App In Improving Learners’ On-Task Behavior - Crestyl Mae Pacheco; Charmaine Amoroso; Divine Grace Pagalan; Jovar G. Pantao; Precy M. Regalado; Diane Mae P. Ulanday-Lozano (International Journal of Learning and Education, 2026)
This study examined the effectiveness of a reward-based classroom management application in improving learners’ on-task behavior, a common challenge for pre-service teachers. Grounded in Behaviorist Theory and positive reinforcement, it explored how a reward-based system influences learner behavior. An explanatory single-case study with qualitative elements was conducted among twenty (20) pre-service teachers at Pedro Acharon Sr. Central Elementary School in General Santos City during the 2025–2026 academic year. Data were collected through pre- and post-intervention interviews over a 20-day implementation, where the application was used in individual and group activities. Before the intervention, learners showed low engagement, limited attention, disruptive behavior, and poor collaboration. After implementation, improvements were observed in focus, participation, task compliance, and behavior. Features such as rewards, immediate feedback, and visual design supported sustained attention and on-task behavior. The study concludes that the application effectively improves learners’ on-task behavior and supports classroom management among pre-service teachers. Therefore, it is recommended that school administrators, teachers, and pre-service teachers integrate reward-based digital classroom management tools to improve learner engagement and classroom behavior, while future researchers further examine their effectiveness in different educational contexts. Keywords: On-task behavior, reward-based classroom management, classroom behavior.